Superior Supercapacitors based on Biowaste Materials - V Bhat; G Hegde; Supriya S (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2019)
Carbon nano spheres derived from Allium cepa were synthesized at different temperatures in a one-step pyrolysis process for supercapacitor electrodes. Obtained carbon nano spheres were analyzed using SEM, FTIR, BET and XRD. The nano materials were fabricated into conducting electrodes for cyclic voltammetry, constant current charge-discharge and electrochemical impedance spectroscopy studies. All the studies were done in 3.0 M KOH electrolyte. Specific capacitance from charge discharge experiments were found to be 132.03 F/g and 149.49 F/g for nano materials synthesized at 500ºC and 600ºC respectively. Obtained values suggest a way forward in producing a green electrode for commercial applications.